Are Asian real exchange rates stationary? - Liew, Venus Khim Sen; Baharumshah, Ahmad Zubaidi; Chong, Terence Tai Leung (Elsevier, 2004)
By applying the newly developed nonlinear stationary test advanced by Kapetanios et al. [Journal of Econometrics 112 (2003) 359] in examining the stationary property of 11 Asian real exchange rates, this paper rejects unit root in 8 US dollar-based and 6 Japanese yen-based rates, whereas the augmented Dickey–Fuller (ADF) test has led to no rejection at all.